2019
DOI: 10.1111/jiec.12845
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of recirculating aquaculture systems: A case of Atlantic salmon farming in China

Abstract: Recirculating aquaculture systems (RAS) are an alternative technology to tackle the major environmental challenges associated with conventional cage culture systems. In order to systematically assess the environmental performance of RAS farming, it is important to take the whole life cycle into account so as to avoid ad hoc and suboptimal environmental measures. So far, the application of life cycle assessment (LCA) in aquaculture, especially to indoor RAS, is still in progress. This study reports on an LCA of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 31 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…Although LCA has been already largely used in industry and agriculture sectors, studies for aquaculture have been developed only recently, and are mainly focused on intensive farming systems, including salmon [29,30], rainbow trout [31], shrimp [32,33], sea bass, sea bream [34,35] and tilapia [36]. In particular, mussel farming has already been examined in an LCA perspective in Spain [37,38], in France [39], in Algeria [40], and in Scotland [41].…”
Section: Introductionmentioning
confidence: 99%
“…Although LCA has been already largely used in industry and agriculture sectors, studies for aquaculture have been developed only recently, and are mainly focused on intensive farming systems, including salmon [29,30], rainbow trout [31], shrimp [32,33], sea bass, sea bream [34,35] and tilapia [36]. In particular, mussel farming has already been examined in an LCA perspective in Spain [37,38], in France [39], in Algeria [40], and in Scotland [41].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to environmental sustainability, many studies evaluated the environmental impacts of aquaponics (Bohnes et al, 2018;Cohen et al, 2018;Kalvakaalva, 2020;Maucieri et al, 2018;Somerville et al, 2014;Song et al, 2019;Wu et al, 2019). Cohen et al (2018) found that combined aquaponic fish-vegetable production would result in significant reduction of impacts in eutrophication, water intake (water use), and geographic footprint (land use) environmental impact categories, compared to large-scale traditional non-integrated production (Cohen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Salmon and trout aquaculture have increased over the past few decades, and demand continues to increase, particularly for cultured Atlantic salmon, where 2.4 million tonnes were produced in 2018 (FAO, 2020). Currently, farmed Atlantic salmon ( Salmo salar ) account for approximately 60% of the world's salmon production (Song et al., 2019). Further, there has been a growing interest in inland Atlantic salmon production, as most production take places in marine cage culture, where there have been many reports of disease issues related to production (Song et al.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there has been a growing interest in inland Atlantic salmon production, as most production take places in marine cage culture, where there have been many reports of disease issues related to production (Song et al. 2019). Worldwide, freshwater farmed salmonids are severely affected by Flavobacterium psychrophilum a widely distributed Gram‐negative, rod‐shaped bacterium that is responsible for considerable economic losses for salmonid production.…”
Section: Introductionmentioning
confidence: 99%